Reflections on Polarisation and Inequalities in Brexit Pandemic Times
1 online resource (xxx, 344 pages).
Keywords: This is the first interdisciplinary edited collection that examines the manifestation of social inequalities and polarisations in Britain throughout the dual crises of the Brexit vote and the Covid-19 pandemic. The volume demonstrates that Brexit and the pandemic are not self-contained events but rather are major ongoing processes that have impacted all aspects of British social and political life. Drawing on an array of empirical case studies conducted in the wake of the Brexit vote and during pandemic lockdowns, chapters trace how these processes illuminate, consolidate, and amplify existing and entrenched social inequalities and polarisations that shape the fabric of British society, including racial, ethnic, class, migrant, national, and gendered inequalities.The volume is divided into three parts centred on (a) the nation; (b) the community; and (c) the media. Each section draws on diverse analytical frameworks and methodological approaches from across the social sciences, arts, and humanities to provide empirically grounded critiques of reductive media-led narratives with the goal of accounting for and explaining the reproduction of social inequalities and emergence of polarisations in these Brexit pandemic times. In so doing, the case studies include critical analysis of lockdown novels; the speeches of political elites from across the political spectrum; 'ordinary' people's everyday traditional and social media practices; as well as their opinions based on the findings of large-scale surveys and in-depth place-based ethnographic fieldwork conducted across rural, urban, and suburban areas of England. Each chapter also includes artwork by contemporary artist Helen Snell that complements, develops, and extends the book's core themes and arguments.This collection will be insightful reading for students and academics across the social sciences, arts, and humanities (especially from the disciplines of sociology, politics, social anthropology, human geography, sociolinguistics, contemporary art, and literature) concerned with questions of social inequality and polarisation.